Teoría y análisis del turismo y su impacto sociocultural (Estudio de Antropología del turismo) - González Arpide, José Luis (Estudios humanísticos. Geografía, historia y arte, 1991)
In recent years growing interest has been shown in Tourism as an agent in regional development. Nevertheless, researchers focusing have largely confined their interest to the positions of Economic or Geography. The research has expanded and become more complex in the question it asks and the theoretical approachs it employs, reflecting both new insights and the changes that have occurred. The transformations occurring at present in the enviroument can be more accuretely interpretated by incorporating an Anthropological perspective, besides from a methodological viewpoint it is essential to make use of such perspective. Our purpose in this paper is to illustrate some theoretical considerations of tourism development’s impact; Tourism as an agent of change: the social and cultural cost to the destination community.